2018
DOI: 10.1099/mic.0.000592
|View full text |Cite
|
Sign up to set email alerts
|

Fusion proteins towards fungi and bacteria in plant protection

Abstract: In agriculture, although fungi are considered the foremost problem, infections by bacteria also cause significant economical losses. The presence of different diseases in crops often leads to a misuse of the proper therapeutic, or the combination of different diseases forces the use of more than one pesticide. This work concerns the development of a ‘super-Blad’: a chimeric protein consisting of Blad polypeptide, the active ingredient of a biological fungicide already on the market, and two selected peptides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…C. glabrata: C. glabrata was grown as described in Pinheiro et al (2016Pinheiro et al ( , 2018. The suspension was prepared by covering the colonies with 5 mL of sterile 0.9% (w/v) saline (NaCl) solution and diluted to a turbidity equivalent to that of a 0.5 McFarland standard with a spectrophotometer at 640 nm.…”
Section: Antifungal Activity Tests -Mic Valuesmentioning
confidence: 99%
“…C. glabrata: C. glabrata was grown as described in Pinheiro et al (2016Pinheiro et al ( , 2018. The suspension was prepared by covering the colonies with 5 mL of sterile 0.9% (w/v) saline (NaCl) solution and diluted to a turbidity equivalent to that of a 0.5 McFarland standard with a spectrophotometer at 640 nm.…”
Section: Antifungal Activity Tests -Mic Valuesmentioning
confidence: 99%
“…A chimeric protein developed by Monteiro et al demonstrated both antibacterial and antifungal activity. This protein was designed by fusing two select peptides with Blad polypeptide, an active component in a commercially available fungicide; by a flexible linker (Pinheiro et al, 2018).…”
Section: Applications Of Fusion Proteinsmentioning
confidence: 99%
“…Due to their diverse activities together with high environmental compatibility and nontoxicity, they have recently sparked increasing interest in the agricultural sector. , Eighteen peptides have been commercialized for use as plant protection agents, with more under development . They can exhibit various modes of action including immune induction, antimicrobial effects, or as plant growth regulators, nematicides, , insecticides, and herbicides . During the course of our research targeting bioactive secondary metabolites of potential anti-infective and/or nematicidal activities, we explored the recently described cyst-associated fungus Laburnicola nematophila (L.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 8 Eighteen peptides have been commercialized for use as plant protection agents, with more under development. 5 They can exhibit various modes of action including immune induction, antimicrobial effects, 9 or as plant growth regulators, 5 nematicides, 9 , 10 insecticides, 11 and herbicides. 12 During the course of our research targeting bioactive secondary metabolites of potential anti-infective and/or nematicidal activities, we explored the recently described cyst-associated fungus Laburnicola nematophila ( L. nematophila ) 13 derived from the plant parasitic nematode Heterodera filipjevi ( H. filipjevi ) to ultimately develop a biocontrol agent.…”
Section: Introductionmentioning
confidence: 99%